Cosmology With Quasars: Predictions for eROSITA From a Quasar Hubble Diagram - Lusso, Elisabeta (Frontiers in Astronomy and Space Sciences, 2020)
The effort for understanding the matter and energy content of the Universe and its evolution relies on different probes, such as cosmic background radiation, cluster lensing, supernovae. Yet, we are still far from grasping what dark matter is made of, and what the physical origin of dark energy is. Our group has developed a technique that makes use of the observed non-linear relation between the ultraviolet and the X-ray luminosity in quasars to provide an independent measurement of their distances, thus turning quasars into standardizable candles. This technique, at present, it is mostly based upon quasar samples with data from public catalogues both in the X-rays and in the optical/ultraviolet and extends the Hubble diagram of supernovae to a redshift range still poorly explored (z>2). From the X-ray perspective, we are now on the eve of a major change, as the upcoming mission eROSITA is going to provide us with up to ~millions of active galactic nuclei across the entire sky. Here we present predictions for constraining cosmological parameters such as the amount of dark matter (Omega_M), dark energy (Omega_L) and the evolution of the equation of state of dark energy (w) through the Hubble diagram of quasars, based on the 4-year eROSITA all-sky survey. Our simulations show that the eROSITA quasars, complemented by redshift and broad-band photometric information, will supply the largest quasar sample at z<2, but with very few objects available for cosmology at higher redshifts that survives the cut for the Malmquist bias, as eROSITA will sample the brighter end of the X-ray luminosity function. The power of the quasar Hubble diagram for precision cosmology lies in the high-redshift regime, where quasars can be observed up to redshift ~7.5, essential to discriminate amongst different model extrapolations. Therefore, to be competitive for cosmology, the eROSITA quasar Hubble diagram must be complemented with the already available quasar samples and dedicated (deep) large programmes at redshift z>3.